A noção de base de um espaço vetorial é trabalhada como "ferramenta explicita" para os assuntos de ciência da computação? - Silva, Carlos Eduardo da (2005)
This research aimed the investigation of the utilization of basis notion of vectorial space in matters of other classes than Algebra Linear of a course of Computation Science. To achieve this, the results collected in seven interviews with professors of this course were analyzed. The analysis of the interviews supported by Dorier, Robert, Robinet and Rogalski ideas about meta resources and the Douady s dialectic tool-object. As result, it was concluded that basis notion of vectorial space is utilized as tool in the sense of Douady, principally in four matters of Computation Science. This conclusion, give us the necessary elements for the construction of didactic sequences that incorporates this situations as meta resources to student s better comprehension about basis notion in Linear Algebra classes